2018
DOI: 10.1190/tle37070529.1
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural networks for automated seismic interpretation

Abstract: Deep-learning methods have proved successful recently for solving problems in image analysis and natural language processing. One of these methods, convolutional neural networks (CNNs), is revolutionizing the field of image analysis and pushing the state of the art. CNNs consist of layers of convolutions with trainable filters. The input to the network is the raw image or seismic amplitudes, removing the need for feature/attribute engineering. During the training phase, the filter coefficients are found by ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 13 publications
0
70
0
2
Order By: Relevance
“…Motivated by good results in many areas, CNNs are becoming researchers' default choice for the segmentation of seismic images and identification of salt deposits. A huge number of papers [34][35][36][37][38][39][40][41] in 2018 and 2019 supports the claim. Dramsch and Lüthje [34] evaluated several classification deep CNNs with transfer learning to identify nine different seismic textures from 65 × 65 pixel patches.…”
Section: Related Workmentioning
confidence: 89%
“…Motivated by good results in many areas, CNNs are becoming researchers' default choice for the segmentation of seismic images and identification of salt deposits. A huge number of papers [34][35][36][37][38][39][40][41] in 2018 and 2019 supports the claim. Dramsch and Lüthje [34] evaluated several classification deep CNNs with transfer learning to identify nine different seismic textures from 65 × 65 pixel patches.…”
Section: Related Workmentioning
confidence: 89%
“…Waldeland et al . () demonstrated how CNNs could be used to classify different seismic textures with special emphasis on salt bodies. Qian et al .…”
Section: Introductionmentioning
confidence: 99%
“…Rentsch et al (2014) trained a neural network to identify SI noise for towed-streamer acquisitions. Waldeland et al (2018) demonstrated how CNNs could be used to classify different seismic textures with special emphasis on salt bodies. Qian et al (2018) applied a deep convolutional autoencoder (DCAE) network in seismic facies recognition based on prestack seismic data.…”
mentioning
confidence: 99%
“…Di, Wang and AlRegib ; Waldeland et al . ; Zeng, Jiang and Chen ; Shi, Wu and Fomel ). However, little work has been done towards an in‐depth comparison of these techniques in seismic saltbody delineation.…”
Section: Introductionmentioning
confidence: 99%
“…Di, Shafiq and AlRegib 2017;Huang, Dong and Clee 2017;Guitton, Wang and Guitton 2017) and saltbody delineation (e.g. Di, Wang and AlRegib 2018a;Waldeland et al 2018;Zeng, Jiang and Chen 2018;Shi, Wu and Fomel 2019). However, little work has been done towards an in-depth comparison of these techniques in seismic saltbody delineation.…”
mentioning
confidence: 99%